Precipitating Factors of Hepatic Encephalopathy in Patients with Cirrhosis of Liver in a Tertiary Care Center of Nepal - Gautam, Niraj; Shrestha, Umid Kumar; Koirala, Dinesh; Gyawali, Susmita (Nepalese Medical Journal, 2024)
Introduction: Chronic liver disease is a common disease presenting in hospitals in Nepal. A large number of cirrhotics present with hepatic encephalopathy. Various precipitating factors are present which precipitate hepatic encephalopathy. This study was intended to identify the precipitating factors of hepatic encephalopathy and to assess whether identifiable precipitating factors of encephalopathy are present. Materials and Methods: This was a hospital-based observational cross-sectional study conducted at the Department of Medicine, Manipal Teaching Hospital, Pokhara. A total of 80 patients were included. The precipitating factors for encephalopathy were documented along with grading. SPSS was used for data analysis. Results: The mean age of the patients was 54.725 ± 11.33 years. There were 55 males (68.8%) and 25 (31.3%) females in the study. All the patients (100%) had a significant amount of alcohol consumption. It was found that hepatic encephalopathy was more severe in the higher Child-Pugh class as compared to a lower one. At least 1 precipitating factor was identified in 81% of patients. The common precipitating factors were increased protein intake, bleeding, infection, diarrhea, and constipation. Conclusions: We conclude that there are different factors that play a key role in precipitating hepatic encephalopathy, with a high protein diet, constipation, bleeding, and infections being predominant. A minor change in dietary habits, regular follow up and timely visits to the health care facility may result in the identification of these common precipitating factors like infections, constipation, and diarrhea.